Reyes Berruezo Albéniz - Soto Alfaro, Francisco (Huarte de San Juan. Geografía e Historia, 2014)
This work summarises the research activity in History of Education that has been carried out by Reyes Berruezo Albéniz during her professional career. The research has been built around two main lines of work. The first one focuses on recovering the important role of Education, its institutions and representatives in the development of individuals and society as a whole through dialectic exercises between society and education. Secondly, the research tries to demonstrate to the would-be-teachers that the complexity of the current educational scheme in society is a historical result in which they will be the future protagonists.